Assessing the level of community capacity building in tourism development in local communities - Aref, Fariborz; Redzuan, Ma’rof; Gill, Sarjit S.; Aref, Abrisham (Canadian Center of Science and Education, 2010)
This study articulates the summary of the thesis which explored levels of community capacity building (CCB) that contributed to tourism development in local communities. The study also provides an overall review of the research objectives, findings, conclusions. The emphasis of this study, however, is on meeting the final objective of the study, namely to formulate principles and guidelines and recommend approaches that can be applied to the development of tourism in Shiraz city, and to create the basis necessary for good practice for any local community toward tourism development projects. The current study begins by summarizing the background to the research, the research objectives, methodology and findings. The researcher goes on to make explicit the contribution of this study to the discipline of tourism development management in local communities of Shiraz and Iran. Suggestions are made for future research based on the theme of this study. The suggestions also provided for enhancing development of building community for tourism.